Chemical characterization of Amazonian non-polar vegetal extracts (buriti, tucumã, Brazil nut, cupuaçu, and cocoa) by infrared spectroscopy (FTIR) and gas chromatography (GC-FID) - Barbara LEONARDI; Luciana Juncioni de ARAUZ; Julia BARUQUE-RAMOS (Federal Council of Pharmacy, 2019)
Amazonian biodiversity products have economic importance mainly in food, pharmaceutical, and cosmetic industries, despite their possibilities of applications has not been extensively developed. This study aimed to perform the chemical characterization of Amazonian non-polar vegetal extracts (buriti oil, tucumã butter, Brazil nut oil, cupuaçu butter, and cocoa butter) employing Fourier transform infrared spectroscopy (FTIR) and gas chromatography with flame-ionization detection (GC-FID). FTIR analysis presented similar spectra whose assignments were based on the correlations with fatty acids. For all extracts, the obtained percentage of fatty acids in the present study presented similarities in comparison to data reported in previous literature. Respect the variations, considered in terms of composition and percentages, could be attributed to the differences of origin of oils, sample conditioning/storage and/or experimental conditions. Finally, the presented findings could be useful to future researches for the chemical characterization and application of Amazon flora extracts, as well as, production of products in food, pharmaceutical, cosmetic, textile and other industrial sectors.